2017
DOI: 10.20396/bjos.v16i0.8651051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proteolytic Agents on Microleakage of Etch and Rinse Adhesive Systems

Abstract: than the occlusal margins (P=0.000) but no significant difference was noted in microleakage of occlusal (P=0.362) or gingival (P=0.147) margins among the three groups by Kruskal Wallis test.Conclusion: in conclusion, application of proteolytic agents(5% bromelain solution and Nd:YAG laser) on acid-etched dentin surface prior to the application of adhesive has no significant effect on marginal microleakage of class V composite restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Our results are consistent with previous studies and may be explained by the depletion of collagen from the acid-etched dentin caused by the action of bromelain and papain. 16,23 However, the SEM observations in this study were inconsistent with the results of the SBS test, which showed that the same 3 groups -those deproteinized with 10% papain, 15% papain and 6% bromelain -had higher SBS values than the other groups, although no statistically significant difference was found between any of the treatment groups and the control group. This could be attributed to other factors, such as the type of adhesive system used.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Our results are consistent with previous studies and may be explained by the depletion of collagen from the acid-etched dentin caused by the action of bromelain and papain. 16,23 However, the SEM observations in this study were inconsistent with the results of the SBS test, which showed that the same 3 groups -those deproteinized with 10% papain, 15% papain and 6% bromelain -had higher SBS values than the other groups, although no statistically significant difference was found between any of the treatment groups and the control group. This could be attributed to other factors, such as the type of adhesive system used.…”
Section: Discussioncontrasting
confidence: 74%
“…In agreement with the current findings, Kasraei et al reported that the treatment of the acid-etched dentin surface with 5% bromelain before the application of the adhesive had no significant effect on marginal microleakage of Class V composite restorations. 23 The SEM micrographs of the resin-dentin interface after the application of bromelain showed that the hybrid layer and resin tags were thick, and the resin tags were conical in shape in the bromelain-treated group. Additionally, spherical residues were observed on resin tags due to the minor infiltration of resin into accessory canals in the dentin.…”
Section: Discussionmentioning
confidence: 94%
“…Dentin conditioning with acidic material may demineralize more of the dentine surface, so the applied adhesive resin monomers can infiltrate and produce a weaker hybrid layer at this important interface(Andermatt & Özcan, 2021). With the purpose of eliminating the influence of the organic matrix on the adhesion of the composites to the dentin, various substances with deproteinizing characteristic were suggested, like papain and bromelain enzymes(Sharafeddin & Safari, 2019).In the present study, no significant difference was observed in the microleakage between phosphoric acid 37% and those treated with bromelain enzyme 10% Kasraei et al (2017). indicated that there was no significant difference in microleakage between the bromelaintreated and acid-etched surfaces Dayem and Tameesh (2013).…”
mentioning
confidence: 44%
“…In the present study, no significant difference was observed in the microleakage between phosphoric acid 37% and those treated with bromelain enzyme 10%. Kasraei et al ( 2017 ) indicated that there was no significant difference in microleakage between the bromelain‐treated and acid‐etched surfaces. Dayem and Tameesh ( 2013 ) revealed that using bromelain enzyme on acid‐etched dentin significantly decreased the microleakage because they used bromelain on acid‐etched dentin and we used bromelain on the dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of direct esthetic restorative materials are available to dentists, including composites and glass ionomer cements 2 . Formulation improvement, leading to the increase in durability of these restorative materials, and made them as the preferable materials for dentists 3 .…”
Section: Introductionmentioning
confidence: 99%